Hubungan ASI Eksklusif Dengan Kejadian Stunting Balita Usia 2-5 Tahun Puskesmas Hiliweto Gido Nias - Sufriyanti Lase; Terimaniat Zebua; Nenisri Lestari Nazara; Luxin Susantri Lase Lase; Nur Sepriani Mendrofa (2026)
One of the factors presumed to be associated with the incidence of stunting is exclusive breastfeeding. This study aimed to determine the relationship between exclusive breastfeeding and the incidence of stunting among children aged 2–5 years in the working area of Hiliweto Gido Public Health Center, Nias Regency, in 2026. This study employed a quantitative method with an analytic observational design using a cross-sectional approach. Data analysis was conducted using univariate and bivariate analyses, with the Chi-Square test at a significance level of α = 0.05.The results showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting among children aged 2–5 years in the working area of Hiliweto Gido Public Health Center, Nias Regency, in 2026. Children who did not receive exclusive breastfeeding were more likely to have a higher risk of experiencing stunting compared to those who received exclusive breastfeeding.In conclusion, there is a relationship between exclusive breastfeeding and the incidence of stunting among children aged 2–5 years. It is expected that the findings of this study can serve as a basis for healthcare professionals to improve the promoting exclusive breastfeeding as one of the strategies for preventing stunting.